Geographic Information System of Patient Development in Jayapura Hospital During Pandemic - Andrian Sah; Suhardi Suhardi; Siti Nurhayati (Universitas Islam Kuantan Singingi, 2021)
Jayapura is a city has population over 240,340 people (Source: Jayapura administration department 2021) and will be increasing in the number of patients in hospitals every year, it will have impact on all hospitals in Jayapura. With this condition, the level of patient development during pandemic and before pandemic will be known. Based on the results of data collection, it is possible to classify categories of disease and treatment in hospitals to choose the best hospital in handling disease and treating patients, especially during pandemic because health management is having difficulties because the medical team focuses more on pandemic patients. Therefore, it is necessary to have geographic information system to collect and provide information to public about the level of development of patients in hospitals, using the PIECES analysis method, designing using Unified Modeling Language (UML) method, using waterfall development method and using QGIS for software used. This research resulted the Geographic Information System for the development of patients in Jayapura City Hospital during Pandemic as means of information for patients in Jayapura.